Anti-commons in tourism: Evidence from Portugal and Bulgaria - Filipe, J.; Yordanova, D. (Modeling and new trends in tourism: A contribution to social and economic development, 2017)
The present study analyzes the cases of Alentejo Region (Portugal) and Bansko Region (Bulgaria) as tourism destinations and demonstrates that situations modelled as anti-commons are obstacles to individual entrepreneurial efforts of agents within the tourism destination as well as impediments for the expansion of the tourism destination as a whole. This paper posits that anti-commons theory is an appropriate theoretical framework for identifying, analyzing and explaining problems emerging in tourism destinations. This framework is useful for modelling optimal development strategies for tourism products and destinations, combining measures provided by national and local authorities with the ones of economic agents. The paper provides recommendations for the future.